Football as Political Communication Tool for German Supporters - Kiki Esa Perdana; Bima Prawira Utama (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
Football is the most popular sport in the world, involving many people, from players, club officials, federation administrators in each country, the media, and also supporters consisting of various backgrounds. In some countries, even football also involves politicians and political parties. Because it involves many people and also many media, it is not uncommon that many people intend to convey their political messages through football so that they can be seen by the public. Germany is one of the countries that experiences this, with a background and political history that is quite strong in society and German football, which is quite famous in the world. Many football supporters in Germany try to convey various political messages to the public; they assume that football is a powerful medium to convey various political messages that they have. Starting from left-wing politics, right-wing nationalism, to various socio-political ideologies. By using political communication methods, this article tries to analyse the correlation between politics and football supporters in Germany. This article was written using descriptive analysis and concluded that although German society has a dark history of politics, this does not prevent German football supporters from conveying their political messages through football, even though the messages are extreme right or left. Keywords: football, punk football, politics.